Arecibo measurements of D-region electron densities during sunset and sunrise: implications for atmospheric composition - Baumann, Carsten; Kero, Antti; Raizada, Shikha; Rapp, Markus; Sulzer, Michael P.; Verronen, Pekka T.; Vierinen, Juha (Annales Geophysicae, 2022)
Earth's lower ionosphere is the region where terrestrial weather and space weather come together. Here, between 60 and 100 km altitude, solar radiation governs the diurnal cycle of the ionized species. This altitude range is also the place where nanometre-sized dust particles, recondensed from ablated meteoric material, exist and interact with free electrons and ions of the ionosphere. This study reports electron density measurements from the Arecibo incoherent-scatter radar being performed during sunset and sunrise conditions. An asymmetry of the electron density is observed, with higher electron density during sunset than during sunrise. This asymmetry extends from solar zenith angles (SZAs) of 80 to 100°. This D-region asymmetry can be observed between 95 and 75 km altitude. The electron density observations are compared to the one-dimensional Sodankylä Ion and Neutral Chemistry (SIC) model and a variant of the Whole Atmosphere Community Climate Model incorporating a subset SIC's ion chemistry (WACCM-D). Both models also show a D-region sunrise–sunset asymmetry. However, WACCM-D compares slightly better to the observations than SIC, especially during sunset, when the electron density gradually fades away. An investigation of the electron density continuity equation reveals a higher electron–ion recombination rate than the fading ionization rate during sunset. The recombination reactions are not fast enough to closely match the fading ionization rate during sunset, resulting in excess electron density. At lower altitudes electron attachment to neutrals and their detachment from negative ions play a significant role in the asymmetry as well. A comparison of a specific SIC version incorporating meteoric smoke particles (MSPs) to the observations revealed no sudden changes in electron density as predicted by the model. However, the expected electron density jump (drop) during sunrise (sunset) occurs at 100° SZA when the radar signal is close to the noise floor, making a clear falsification of MSPs' influence on ...